A figura da bruxa na Literatura Contemporânea – Fronteiras de ressignificação - Hirasike, Roseli (2024)
This research examines the figure of the witch in literature, starting its journey from goddesses in mythology, as the first literary sorceress characters in the works of Homer and Hesiod. Although playing secondary roles in the epics, the goddesses were revered for their divine witchcraft, with which they aided the heroes and served the gods. In these poetic works, we observe the consolidation of the figure of the hero as one capable of superhuman feats, endowed with strength, courage, and exceptional fighting skills, protected by the patrilineality led by Zeus – all gods descended from him and were protected and controlled by him. We follow the History of Witchcraft focusing on the transformation of the divine witch into diabolical during the Middle Ages, through literary genres such as troubadour poetry and chivalric romances, intertwined with the adoration of female figures, inspiring muses of the medieval noble knights' struggle. In this context, we delve into the Church's reaction to social trends and profane arts in the period, and how conflicts and anxieties arising from the impasse between sacred and profane resonated in literature, including religious works. The intellectual elite of the church's concern regarding female protagonism threatening patriarchy triggered moralizing actions that instilled in the collective thinking the inherent malignancy of women's behavior temptations, considering them as foolish beings more vulnerable to the influence of the Devil. Thus, heretical women were associated with diabolical pacts in an ideological arena that would culminate in the witch hunts, an episode with terrible consequences for human history, now recognized as a genocide. As the witch is the stereotype built from the medieval imagination and used for the persecution and extermination of women who were alone, poor, non-Christians, or socially transgressive of the order of the time, silenced by History, the re signification of the witch figure that we highlight is the one that emerges from the female voice in contemporary narratives. Our hypothesis envisions the recognition of an original structure of the heroine, whose definition elevates aspects of the feminine beyond gender heroism. From the perspective of the main stages of the journey, the heroine reveals particular and disconnected aspects, therefore, from the male attributes exaggerated in the figure of the hero. The development of the thesis is divided into two parts. Part I focuses on the role of the witch goddesses in Greek Mythology in the classic literature of Homer and Hesiod, and the History of Witchcraft in the Middle Ages, with a focus on the emergence of the diabolic witch stereotype. Part II analyzes contemporary novels that form the research corpus, their narratology, and the construction of the protagonists, in historical metafiction and the romanticized retelling of the myth. The narratives give voice to heroines who, in their sagas, resist and denounce the use of witchcraft accusations and the culture of fear as a subterfuge to silence transgressive women, thus maintaining the patriarchal order. They are: Tituba Indien, a historical character from the colonization of New England, during the Salem Witch Trials Hysteria; and Circe, as the narrator of the contemporary retelling of her myth